Analysis of the Mathematics Questions in 2021 High School Entrance Exam According to Learning Areas and the MATH Taxonomy - ALİUSTAOĞLU, Feyza; DAĞDELEN, İrfan; TULUK, Güler (Kastamonu Egitim Dergisi, 2023)
Design/Methodology/Approach: Learning areas were coded as “learning area” and “linked learning area.” In the context of cognitive processes, the exam questions were classified according to the groups and categories of the MATH Taxonomy developed specifically for mathematics. The research was designed as document analysis, one of the qualitative research designs. Findings: It was found that the questions in 2021 LGS were taken from all learning areas of secondary school mathematics and the numbers of questions were compatible with the learning areas in the curriculum. It was seen that many questions addressed more than one learning area, and the learning areas were related to each other. When the questions in 2021 LGS were examined in the context of cognitive processes according to the MATH taxonomy, it was found that there were questions from the groups B and C, mostly C, and no questions from the group A. The questions in 2018, 2019, and 2021 LGS were also compared in this study. It was found that the learning areas generally had a similar distribution, and when compared in terms of MATH taxonomy; as the years progressed, the level of the questions increased. Highlights: The use of MATH Taxonomy, which was developed specifically for mathematics, has an important role in examining mathematics questions according to cognitive processes. It was observed that the questions were not directed to a single learning area, and that the learning areas were related to each other. It is thought that coding in the form of learning area-linked learning area is important.
Keywords: Eğitim Üzerine Çalışmalar; Mathematics Education; MATH Taxonomy; Learning area; High School Entrance Exam (LGS; Studies on Education; 4. Education